(untitled) (Trabalho & Educação, 2016)
This paper extends the analysis and complements the symbolic social representations (SR) of teachers wear (Author), considering the material aspects, organizational and structural of teaching. Thirty-eight teachers from Paraná State school system took part in the investigation. Data was collected through semi-structured interviews developed from successive sorting. The SR theoretical approach is the Moscovici’s dimensional associated to discussions on the precarious working conditions and teaching. The interviews focused on the aspects that structure teaching, analyzing their content with the aid of the Software Alceste. The classes obtained were: salary, school management, working time outside the classroom, complementary activities, crowded classrooms and the relationship with students. The analys is of information presents patial dislocations between the public and private, with the time comprehended, extending school activities to the home space. The classrooms appear either as a space of negation of the teaching activity or intensification of the teaching job. ___ Este artigo amplia as análises e complementa os aspectos simbólicos das representações sociais (RS) do desgaste docente (Autor), contemplando os aspectos materiais, organizacionais e estruturais da docência. Participaram da investigação 38 docentes do sistema estadual de ensino paranaense. Os dados foram coletados mediante entrevistas semiestruturadas associadas a triagens sucessivas. A abordagem teórica das RS é a dimensional de Moscovici associada às discussões sobre precarização do trabalho e da docência. Das entrevistas retiveram-se os aspectos estruturais da docência e a analise lexical foi realizada com o auxílio do software Alceste. Formaram-se as classes salário, gestão escolar, hora atividade, atividades complementares, salas lotadas e a relação com os alunos. A análise apresenta os deslocamentos entre o público e o privado, com a compressão temporal prolongando as atividades escolares ao espaço doméstico. As salas de aulas constituem o espaço de negação da docência ou intensificação de trabalho docente.